2021
DOI: 10.2166/nh.2021.029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of satellite-based precipitation products from GPM IMERG and GSMaP over the three-river headwaters region, China

Abstract: The three-river headwaters region (TRHR) is the birthplace of the Yangtze River, the Yellow River and the Lantsang River in China. Based on the grid surface precipitation data released by China Meteorological Administration (CMA), this paper evaluated the accuracy and error components of four near-real-time satellite precipitation products (GSMaP-NRT, GSMaP-MVK, IMERG-Early and IMERG-Late) in the era of a GPM (Global Precipitation Measurement) in TRHR. The conclusions are as follows: (1) The precipitation in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…The evidence supporting this finding is presented in Figure 11d that indicates that the errors of IMERG‐F in regard to underestimating rainfall over Luzon originally existed in IMERG‐L. Possible reasons for the underestimation of rainfall by IMERG‐L have been suggested in earlier studies (Bogerd et al., 2021; Wang et al., 2021) that indicate that IMERG‐L tends to miss shallow rainfall events, and this may lead to underestimation of rainfall. Additionally, we note from Figures 11d and 11e that GSMaP‐M is better than is IMERG‐L for assessing eastern Luzon but not for western Luzon.…”
Section: Resultssupporting
confidence: 62%
“…The evidence supporting this finding is presented in Figure 11d that indicates that the errors of IMERG‐F in regard to underestimating rainfall over Luzon originally existed in IMERG‐L. Possible reasons for the underestimation of rainfall by IMERG‐L have been suggested in earlier studies (Bogerd et al., 2021; Wang et al., 2021) that indicate that IMERG‐L tends to miss shallow rainfall events, and this may lead to underestimation of rainfall. Additionally, we note from Figures 11d and 11e that GSMaP‐M is better than is IMERG‐L for assessing eastern Luzon but not for western Luzon.…”
Section: Resultssupporting
confidence: 62%
“…In addition, the correlation of daily GSMaP data and RG points is also very dependent on the number of gauges in grids used in validation (SatgĂ© et al 2019). Several studies in China that compared GSMaP Grid data with RG points also found a moderate correlation (Lu and Yong 2018; An et al 2020;Zhou et al 2020;Wang et al 2021a). In addition, moderate correlation values were also found in Vietnam (Gummadi et al 2022) and Thailand (Trang et al 2020).…”
Section: Daily Assessmentmentioning
confidence: 99%
“…The intensified atmospheric hydrological cycle exerts a significant effect on precipitation (Held & Soden, 2006;Immerzeel et al, 2010Immerzeel et al, , 2020Lan et al, 2016;Xi et al, 2018). Numerous studies demonstrated that the precipitation over TRHR manifested a variation on multiple scales, particularly featured by a significant increase during the last decades (Cao & Pan, 2014;Shi et al, 2016;Xi et al, 2018;Ma et al, 2018;Yiyang et al, 2020;Yan et al, 2020;Hua et al, 2021;Xianhong et al, 2022;Shang et al, 2021aShang et al, , 2022Li et al, 2022b;Guo et al, 2022) and a dry-to-wet shift in around the late 1980s in the context of global climate change (Zhang et al, 2017a;Sun & Wang, 2018;Ji et al, 2020;Shang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%